Multi-objective topology optimization using the Boundary Element Method. (June 2019) - Simonetti, Hélio Luiz; Almeida, Valério S.; de Assis das Neves, Francisco; Greco, Marcelo
Abstract: This article aims to explore the application of an evolutionary optimization technique for multi-objective optimization problems using as criteria the minimization of von Mises maximum stress and minimization of the maximum growth of internal structural strain energy. To evaluate the overall effect on the optimal design configuration, due to the removal of inefficient material from the structure by using these two optimization criteria, a goal weighting scheme is adopted, whereby the weight factors emphasize and balance the stress and strain energy criteria. Also considered in this study was the method of the exponentially weighted criterion for multi-objective optimization and the Pareto optimal concept. Thus, a contribution is made to the study of these two methods in the structural optimization procedure using a linear analysis by the Boundary Element Method. Four examples are presented to demonstrate the ability of the proposed method to solve structural design problems using multi-objective optimization.